If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -15 = 13x + -10 + 33 Reorder the terms: -15 + 9x = 13x + -10 + 33 Reorder the terms: -15 + 9x = -10 + 33 + 13x Combine like terms: -10 + 33 = 23 -15 + 9x = 23 + 13x Solving -15 + 9x = 23 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -15 + 9x + -13x = 23 + 13x + -13x Combine like terms: 9x + -13x = -4x -15 + -4x = 23 + 13x + -13x Combine like terms: 13x + -13x = 0 -15 + -4x = 23 + 0 -15 + -4x = 23 Add '15' to each side of the equation. -15 + 15 + -4x = 23 + 15 Combine like terms: -15 + 15 = 0 0 + -4x = 23 + 15 -4x = 23 + 15 Combine like terms: 23 + 15 = 38 -4x = 38 Divide each side by '-4'. x = -9.5 Simplifying x = -9.5
| 0.01w=-0.045 | | 4x+8=90-4x | | (-2m^4n^5)(7mn^3)= | | 6x-12=4x+11 | | 140-4x=5x | | (8x)= | | 140-4x=10x+17 | | x^2-15x+65=11565 | | factorisem^2+7m-10=0 | | 5cos(x+17)=4 | | m^2+7m-10=0 | | 5(3x+2)=-5 | | 5x-9=111-10x | | x(4-x)=x^2(7-x) | | 13210*X^2+6785600*x-5315460000=0 | | 4(3x-1)=56 | | (-7m^5n^5)(5mn^2)= | | (-4a^6b^6)(3ab^3)= | | x^2+5y=x^2 | | (b^9c^5)(b^7c)= | | 180-x^2+x-5=7x+5 | | x-5+x+5=39 | | (m^10n^3)(m^12n)= | | 32*x^5+1=0 | | 3(3*3)=-27 | | x+8+x^2-3x+3x-2+x+2=43 | | 17x+5=17x+5 | | 3x^2+4=999 | | 10=10x-x^2 | | k*k+5=9 | | 2(2x+2)+.5(x+1)=4(x+2) | | 8x-13+3x-5=180 |